Brassinin Combined with Capsaicin Enhances Apoptotic and Anti‐metastatic Effects in PC‐3 Human Prostate Cancer Cells. (1st October 2015) - Kim, Sung‐Moo; Oh, Eun Young; Lee, Jong Hyun; Nam, Dongwoo; Lee, Seok Geun; Lee, Junhee; Kim, Sung‐Hoon; Shim, Bum Sang; Ahn, Kwang Seok
Abstract : Brassinin (BSN), a type of indole compound derived from cruciferous vegetables, has shown anti‐cancer effects in cells and animals. Capsaicin (CAP), an alkaloid derived from the chilli pepper, is also of interest in for its reported efficacy against various malignancies. The objective of our study was to analyze the potential synergistic anti‐tumor effects of BSN combined with CAP on prostate cancer PC‐3 cells. After treatment with BSN and CAP at various concentrations, the synergistic cytotoxic effect of PC‐3 cells was analyzed by MTT method, proliferation, apoptosis, mitochondrial membrane potential, colony formation, and Western blotting. Moreover, the inhibitory effects of BSN and CAP on the constitutive expressions of MMP‐9/2, their enzymatic activities, cellular migration, and cell invasion were also investigated. The cytotoxicity was synergistically increased in combination compared with the single drug used; moreover, proliferation, apoptosis, mitochondrial membrane potential, and colony formation were significantly suppressed and anti‐apoptotic‐, proliferative‐, and metastatic‐related proteins were clearly abolished in the combination group. Besides, constitutive MMP‐9/2 expression, their enzymatic activities, cell migration, and tumor cell invasion were inhibited, and TIMP‐1 was up‐regulated in the combination group in PC‐3 cells. Our results indicate, for the first time, that BSN and CAP in combination exert synergistic anticancer effects in prostate carcinoma. Copyright © 2015 John Wiley & Sons, Ltd.